Role of Ponceau-S-Mannitol System for Generation of Electrical Energy in Photogalvanic Cell - Chandra, Mahesh; Meena, R. C. (Journal of Nepal Chemical Society, 2010)
Ponceau-S is used as a photo sensitizer in photogalvanic cell for solar energy conversion and mannitol is used as an electron donor in this study. The effects of various parameters like pH, light intensity, diffusion length, reductant concentration and dye concentration on the electrical output of the cell is studied. The photopotential and photocurrent generated by this cell are 1080 mV and 240 μA, respectively. The current voltage (i-V) characteristic of the cell is also studied and a mechanism for the generation of photocurrent is proposed. Keywords: Photogalvanic cel; Photopotentia; Ponceau-S; Mannito; Photocurrent DOI: 10.3126/jncs.v26i0.3631 Journal of Nepal Chemical Society Vol. 26, 2010 Page: 46-52